Pengaruh Konsentrasi Pupuk Organik Cair Limbah Rumah Tangga Terhadap Pertumbuhan dan Hasil Tanaman Sawi Hijau Pada Sistem Hidroponik NFT - Putu Eka Pasmidi Ariati; Ni Putu Eka Pratiwi; Made Astagunawan (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2024)
The purpose of this study was to determine the effect of applying Cow Manure Organic Fertilizer on the growth Hydroponics has promising prospects for future agriculture, but the high cost of production makes hydroponics a burden. This study aims to determine the effect of POC (liquid fertilizer) concentration from household wasted on the growth of mustard greens which was expected to determine the best concentration of POC from household waste for mustard greens in the NFT hydroponic system. This research was conducted for one month at BPTP Bali. There were five treatments (P1, P2, P3, P4) including the control treatment (P0), with six replicates with a randomized block design (RBD). The data was collected consisted of plant height, number of leaves, fresh weight and dry weight of plants. The results of the data were then analyzed by ANOVA, followed by the BNT test at the 5% level. The results showed that there was an effect of household waste POC liquid organic fertilizer on the growth of mustard greens at P1 (100 ml/900 ml) compared to P2, P3 and P4 but it was still better with the control using AB-mix. From the results of the study it can be concluded that the best was P1 with concentration of 100 ml/900 ml of water. It is necessary to carry out further research regarding the use of Liquid Organic Fertilizer (POC) and improving the quality of POC nutrients so it can be able to provide sufficient nutrients for the mustard greens hydroponic system